Moving from 'developmental' to 'anti-developmental' local financial models in East Asia: Abandoning a winning formula. Issue 137 (December 2022) - Bateman, Milford
Abstract: One of the decisive but often overlooked factors in the creation of the East Asian 'economic miracle' was the part played by a variety of heterodox sub-national state, community and cooperatively owned and controlled financial systems, institutions and lending models. Beginning with Japan after 1945, local financial systems were (re)constructed across East Asia in a way that very efficiently operationalised key development policy goals through targeted local enterprise development. Yet in spite of marked success with this 'developmental' local financial model, from the 1980s onwards the international development community, led by the US government and the World Bank, began an effort to discredit and replace it with a new commercially-oriented private sector-led local financial model promoting mass individual entrepreneurship with the help of a for-profit microcredit sector. This article begins by briefly summarising why such 'developmental' local financial models were important to East Asia's economic miracle before I turn to examining why, how and what happened when after 1980 the international development community quietly set out to undermine and destroy them. I conclude from this analysis that the international development community's desire to begin to impose its own neoliberal ideology and narrow elite-driven enrichment goals in East Asia far outweighed the ongoing development successes registered by the 'developmental' local financial models that emerged after 1945.